In vivo inhibition of neuronal activity in the rat ventromedial prefrontal cortex by midbrain-raphe nuclei: role of 5-HT1A receptors. - Hajós, M; Gartside, SE; Varga, V; Sharp, T (2003)
The ventral part of the medial prefrontal cortex (mPFC) plays an important role in mood and cognition. This study examined the effect of the 5-HT in this region by measuring the electrophysiological response of ventral mPFC neurones to electrical stimulation of the dorsal and median raphe nuclei (DRN and MRN), which are the source of the 5-HT input. DRN or MRN stimulation evoked a consistent, short-latency, post-stimulus inhibition in the majority of ventral mPFC neurones tested (DRN: 44/73 neurones; MRN: 24/31 neurones). Some neurones responded to DRN or MRN stimulation with antidromic spikes indicating that they were mPFC-raphe projection neurones. Both DRN- and MRN-evoked inhibitions were attenuated by systemic administration of the 5-HT1A antagonist WAY 100635 (0.1 mg/kg i.v.). DRN-evoked inhibition was also attenuated by iontophoretic application of WAY 100635 and by systemic administration of the 5-HT1A antagonist, NAD-299 (4 mg/kg i.v.) but not the 5-HT2 antagonist ketanserin (4 mg/kg, i.v.). These data suggest that DRN and MRN 5-HT neurones inhibit neurones in the ventral mPFC via activation of 5-HT1A receptors. Some of these mPFC neurones may be part of a 5-HT1A receptor-controlled postsynaptic feedback loop to the DRN and MRN.